Achieving exceptionally high luminescence quantum efficiency by immobilizing an AIE molecular chromophore into a metal–organic framework. Issue 15 (5th December 2014) - Hu, Zhichao; Huang, Guangxi; Lustig, William P.; Wang, Fangming; Wang, Hao; Teat, Simon J.; Banerjee, Debasis; Zhang, Deqing; Li, Jing
Abstract : We build a new rare-earth-free blue-excitable phosphor, which emits yellow light with high quantum yield. Coating a blue LED with this phosphor generates white light with high luminous efficacy. Abstract : We design a new yellow phosphor with high quantum yield by immobilizing a preselected chromophore into a rigid framework. Coating a blue light-emitting diode (LED) with this compound readily generates white light with high luminous efficacy. The new yellow phosphor demonstrates great potential for use in phosphor-converted white LEDs.